Synthesis of superfine paramagnetic nickel particles using anionic and cationic surfactants. (28th August 2019) - Shafique, M Khizar; Muhmood, Tahir; Lin, S; Xiaobin, Hu; Gull, Sehrish
Abstract: Superfine paramagnetic nickel particles were synthesized using different anionic and cationic surfactants with propylene glycol as solvent. Surfactants including gum arabic, gelatin, PVP and tri-sodium citrate were used. SEM analysis proved that the morphology of nickel particles was perfectly spherical with little agglomeration. The morphology of microspheres was changed with variation of anionic and cationic surfactants, but majorly the spherical shape of nickel particles was retained. The purity of superfine nickel particles was also confirmed with EDS. The XRD analysis results also indicated the presence of 'fcc' crystal in these superfine particles. The magnetic field analysis designated the existence of magnetic properties in synthesized superfine nickel particles. Surface area properties were also measured with the help of BET analysis which determined the enhanced catalytic property of these particles. Overall the synthesized nickel superfine microspheres possess improved morphology and magnetic properties with the addition of PVP as surfactant as compared to gum arabic, gelatin, and tri-sodium citrate.